Geradores lineares tubulares a pistão livre: modelagem harmônica e análise da densidade de fluxo magnético de um arranjo Halbach - Souza, Williamar Prazeres (2024)
Permanent magnet linear generators are known for their efficiency, compact construction and ability to use different types of drives for power generation. This study focuses on the modeling and analysis of a free piston driven permanent magnet linear polygonal electric generator. The generator design model was defined based on analytical mathematical bases aiming at obtaining the behavior of the machine according to the magnetic flux density present in the generation process, as well as on simulations in specific software for analysis of electrical machines. In this study, the generator magnets were molded using a configuration based on the Halbach type arrangement. The designed generator has a polygonal linear axis with twelve rows of Neodymium magnets arranged in such a way as to form two magnetic polar steps. In order to verify the performance, numerical analyses were performed using the finite element method in the ANSYS® Maxwell software. Furthermore, the complete dynamic model was implemented using Matlab®, through Simulink®. The system was controlled using a controlled current source - AC/DC converter. The construction of the generator prototype is based on the results generated through mathematical analyses of harmonic modeling and numerical simulation methods. The values of electromagnetic parameters, such as current, voltage, magnetic density and power, were obtained at the resonant mechanical frequency, based on the thrust force of the linor predicted in the future construction of the free piston engine to be coupled to the generator, which will occur at a frequency of 33.8978 Hz. The data were then analyzed to evaluate the generator performance. The conclusions demonstrate satisfactory results according to the Finite Element method and the dynamic simulation model chosen, given that the generator prototype is still under construction.